Hepatic artery resistive index as surrogate marker for fibrosis progression in NAFLD patients: A clinical perspective. (5th June 2018) - Tana, Claudio; Schiavone, Cosima; Ticinesi, Andrea; Lauretani, Fulvio; Nouvenne, Antonio; Dietrich, Christoph Frank; Meschi, Tiziana
Ultrasound (US) can reveal the presence of steatosis in non-alcoholic fatty liver disease (NAFLD), but its diagnostic accuracy to reveal signs of fibrosis is low except in advanced stages of disease (e.g. cirrhosis). Current guidelines suggest the use of clinical algorithms, such as the NAFLD fibrosis score, and elastography to predict the progression of fibrosis, and the integration of elastography improves the detection accuracy of liver stiffness. However, there is a lack of evidence about the correlation between clinical algorithms and conventional US, and elastography is limited by the relative low diffusion, necessity of training, and loss of diagnostic accuracy in patients with high body mass index (BMI), waist circumference, or increased thickness of parietal walls, with consequent significant rates of failure of measurement of liver stiffness. Recently, the measurement of hepatic artery resistive index (HARI) has demonstrated a significant positive correlation with fibrosis degree, as measured with NAFLD fibrosis score, suggesting that the fibrous tissue accumulation may result in increased arterial rigidity and, therefore, in a rise of resistance to flow, and that the different tissue composition of the liver (adipose versus fibrous) can influence HARI differently. These issues should be further investigated because some aspects are still unknown. The limited data currently justify the need of larger, prospective studies aimed at assessing whether HARI correlates with elastography results. In view of their effect on weight loss, serum lipid concentration, and hepatic arterial flow hemodynamics, it could be interesting to evaluate if lifestyle and diet changes can influence significantly HARI values in NAFLD patients.